Effect of Gender, Region and Type of School on Social, Cognitive and Affective Skills of Higher Secondary School Students - Shabana,; Alam, Khalida (INDIAN EDUCATIONAL REVIEW, 2018)
The present study examined the inter-relationship between the social, cognitive and affective skills of higher secondary schools students in selected districts of Chhattisgarh employing a descriptive survey research. By adopting stratified disproportionate random sampling technique, 420 students were selected from three districts of Chhattisgarh namely Durg, Rajnandgoan and Kabirdham (Kawardha). Data collection was completed in five months by administrating self-constructed life skill assessment scale, which comprised of three dimensions, namely social, cognitive and affective Skills. Social skills comprised of communication skills, empathy, interpersonal skills and resisting peer pressure. Cognitive skills included problem solving, creativity, decision making and critical thinking. Included among affective skills were items related to coping with stress, managing emotions and self-awareness. Initially 190 items were prepared. Content and face validity reduced the items to 133. Inter item validity was computed using ‘t’ test. Final scale comprised of 75 items. Reliability coefficient computed by test-retest method was found to be 0.85. Statistical analysis of the data was done by computing three way ANOVA and t-test. Results indicated significant impact of gender, region and type of schools on social, cognitive and affective skills of higher secondary school students.